STABILITAS DAN ADAPTABILITAS HASIL JAGUNG HIBRIDA DR UNPAD DI TIGA LOKASI PADA DUA MUSIM TANAM DI JAWA TIMUR, INDONESIA - R. Aprilianti; D. Ruswandi; Anggia E. P.; Tri Hastini; A. Suhada; N. Istifadah; A. Ismail; E. Suryadi; S. Ruswandi; N. Rostini (Zuriat, 2011)
Study adaptability is an important step to select superior hybrids which have wide adaptability or specific adaptability. Fifhteen of DR Unpad hybrids have purpose to know about stability and adaptability for yield characters (yield ton/ha), ear weight of plot (kg), ear weight of sample (kg), and grain weight of sample (kg) of DR Unpad hybrids in East Java and to determine GxE interaction on two plant seasons for build up superior variety in Indonesia. Three location and each location two seasons, fifhteen hybrids and four tester cultivar were tested and randomized complete block design with three replications. Data were analysis of variance, complete analysis variance, and AMMI. The results indicated that there was GxE interaction  for yield character. Thus, for yield performance, hybrids Var R showed high stability and high yield. Var R, C, and Var G have a wide adaptability for yield. Var C and R had specific  adaptation in marginal location in Sidoarjo  on second season. And hybrids Var F and Var B specific for Ngronggot on second season which that location was a good environment.